The Key on the Quilt : The Quilt Chronicles - Whitson, Stephanie Grace (Uhrichsville, OH : Barbour Pub., 2012)
Three women within the prison system--Jane, a prisoner; Mamie, a prison matron; and Ellen, a prison warden's wife--develop an unexpected friendship, face struggles with staying faithful, and deal with romantic entanglements.
Keywords: Female friendship -- Fiction; Prisoners -- Fiction; Quilts -- Fiction; Prisons -- Fiction -- Employees; Wives -- Fiction; Nebraska -- Fiction; Christian fiction; Love stories